2002
DOI: 10.1063/1.1506786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of competing energies on the transition noise of oriented magnetic media

Abstract: There has been some disagreement in observation of the effect of oriented media on the recording performance from earlier and recent studies. In this letter, we have identified the reasons behind these disagreements by studying the effect of the energy ratio of local anisotropy (Ku) and long range magnetostatic interaction energies (Kd) (Q=Ku/Kd). The magnetization reversal mechanism is observed to be different in the recorded bit transition of different magnetic properties (Q) of the media. The results on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…It is also noted that a similar conclusion was found in the highly oriented longitudinal media [19], [20]. It should be pointed out that even with the marginal increase of OR from 1.0 ( ) to 1.35 ( rad), SNR improvement is very significant from about 2 dB to about 20 dB.…”
Section: A In-plane or Effect On A Longitudinal Recording System Witsupporting
confidence: 62%
See 1 more Smart Citation
“…It is also noted that a similar conclusion was found in the highly oriented longitudinal media [19], [20]. It should be pointed out that even with the marginal increase of OR from 1.0 ( ) to 1.35 ( rad), SNR improvement is very significant from about 2 dB to about 20 dB.…”
Section: A In-plane or Effect On A Longitudinal Recording System Witsupporting
confidence: 62%
“…It was reported that in-plane magnetic orientation could improve the recording performance in longitudinal recording [19]. Since it is difficult to fabricate the ideal tilted media with magnetic easy axis either along the down-track or cross-track direction by normal sputtering techniques, in plane orientation may become one of the most critical factors to determine the feasibility of the fabrication of tilted media.…”
Section: In-plane Orientation Effect On Tilted Mediamentioning
confidence: 99%
“…[50][51][52][53] While the simulation of Charap and Lu used isotropic media, later work on simulation and experimental studies pointed out that oriented media ͑ORϾ 1͒ showed larger thermal stability than isotropic media. 2 .…”
Section: A Oriented Mediamentioning
confidence: 99%
“…The monodispersed L1 0 -FePt NPs are promising candidates for high-density magnetic recording, which could push the super­paramagnetic limit. Sun and co-workers pioneered the use of L1 0 -FePt nanocrystals for magnetic recording . Because the ordered temperature of L1 0 -FePt is above 550 °C, they prepared A1-FePt NPs and then converted them to L1 0 -FePt nanocrystal superlattices with the thickness of 180 nm (Figure C) by the annealing treatment.…”
Section: Synthesis and Magnetism Exploration Of Mnssmentioning
confidence: 99%